2019
DOI: 10.1016/j.hpb.2019.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Early postoperative fluid retention is a strong predictor for complications after pancreatoduodenectomy

Abstract: Background: Perioperative fluid overload has been reported to increase complications after a variety of operative procedures. This study was conducted to investigate the incidence of fluid retention after pancreatic resection and its association with postoperative complications. Methods: Data from 1174 patients undergoing pancreatoduodenectomy between 2010 and 2016 were collected from the Swedish National Pancreatic and Periampullary Cancer Registry. Early postoperative fluid retention was defined as a weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Consistent with other studies, we found that recipients with excessive FB have more complications [34][35][36][37][38]. The harmful effects of fluid overload are often manifested as pulmonary edema, pleural effusions, and cardiac overload, thereby putting patients at a high risk Figure 2 The eGFR at 1, 6, and 12 months after kidney transplantation in four fluid balance levels.…”
Section: Discussionsupporting
confidence: 86%
“…Consistent with other studies, we found that recipients with excessive FB have more complications [34][35][36][37][38]. The harmful effects of fluid overload are often manifested as pulmonary edema, pleural effusions, and cardiac overload, thereby putting patients at a high risk Figure 2 The eGFR at 1, 6, and 12 months after kidney transplantation in four fluid balance levels.…”
Section: Discussionsupporting
confidence: 86%
“…Early fluid retention in patients undergoing pancreatoduodenectomies has previously been associated to increased postoperative morbidity, and may represent an important factor in the early perioperative setting. 23,39 In this present study, we were unable to include information on perioperative fluid administration, which limits the assessment of postoperative weight change. While some evidence suggests that a liberal intraoperative fluid balance may be associated with an increased rate of postoperative morbidity after pancreatoduodenectomy, there are also convincing data showing how, in case of a high-risk pancreas, a near-zero fluid balance could lead to pancreatic stump ischemia, with increased postoperative pancreatic fistula and hyperamylasaemia rates.…”
Section: Discussionmentioning
confidence: 92%
“…A weight increase of ≥2 kg was considered clinically significant as this cut-off has previously been associated to an increased risk of postoperative complications. 23…”
Section: Outcomes Of Interestmentioning
confidence: 99%
“…The negative effects of excessive fluid overload in the postoperative period have long been recognized [13][14][15][16]. A contemporary randomized study investigating fluid regimens in patients undergoing colorectal surgery found that a restrictive fluid strategy not only led to decreased cardiopulmonary morbidity but also reduced the incidence of tissue-healing complications [17].…”
Section: Discussionmentioning
confidence: 99%